Características epidemiológicas, clínicas y terapéuticas en niños menores de 2 años con diagnóstico de bronquiolitis en el servicio de pediatría del Hospital II-2 Tarapoto, enero – diciembre 2016 - Monja Garcia, Jose Luis (2016)
Objective: To identify the epidemiological, clinical and therapeutic characteristics in children younger than 2 years old with diagnosis of bronchiolitis in the Pediatric Service of Tarapoto II-2 Hospital, January - December 2016. Methodology: it is a Descriptive, non-experimental study; where Seventy-one children under 2 years of age with a diagnosis of bronchiolitis were considered. The collection of information was done through a data collection tab. Results: 49.3% were younger than 6 months, the mean age being 6.05 months. 74.6% of the patients were male. In July (18.4%), September (16.9%) and November (12.7%) had a higher incidence; Likewise, 62.1% came from rural areas. The most frequent risk factors were non-exclusive breastfeeding (23.9%) and prematurity (18.3%). Cough (97.2%), dyspnea (83.1%) and wheezing (76.1%) were the clinical manifestations with the highest percentage. Corticosteroids were received in 90.1% of the children, while 85.9% received nebulization 3% NaCl and 50.7% bronchodilators. Fifty-three percent of the children remained between 4 and 7 days, while 46.6% presented oxygen saturation between 88% and 92%. The most frequent complication was pneumonia (17.0%) and 66.2% had a mild degree of severity. Conclusion: The results obtained are similar to those published in the current literature